WEBTOONS POTENTIALS TO ENHANCE EFL STUDENTS VOCABULARY - Elza Aqilla Novanti; Suprayogi Suprayogi (Universitas Teknokrat Indonesia, 2021)
This paper aims to show the use of Webtoon for EFL students to get more vocabulary either by the dialogue or even just the picture itself because it also can increase the level of curiosity and let them create new words. Webtoon has been known as one of the e-comic applications that are loved by young generations because it is simple yet fun. The use of outstanding visual and daily basis dialogues will surely help students understand the meaning of the whole scene. The method of the research used qualitative descriptive. The technique of collecting data and the data are questionnaires from EFL Learners that also use webtoon on their daily activity as well as English teachers who use webtoon in their class. Overall EFL learners who are also webtoon users found that the application helps them to create new words by seeing the visualization along with the dialogue.